Influence of gut and lung dysbiosis on lung cancer progression and their modulation as promising therapeutic targets: a comprehensive review - Thapa, Rajan; Magar, Anjana Thapa; Shrestha, Jesus; Panth, Nisha; Idrees, Sobia; Sadaf, Tayyaba; Bashyal, Saroj; Elwakil, Bassma H.; Sugandhi, Vrashabh V.; Rojekar, Satish; Nikhate, Ram; Gupta, Gaurav; et al. (MedComm (2020), 2024)
Lung cancer (LC) continues to pose the highest mortality and exhibits a common prevalence among all types of cancer. The genetic interaction between human eukaryotes and microbial cells plays a vital role in orchestrating every physiological activity of the host. The dynamic crosstalk between gut and lung microbiomes and the gut–lung axis communication network has been widely accepted as promising factors influencing LC progression. The advent of the 16s rDNA sequencing technique has opened new horizons for elucidating the lung microbiome and its potential pathophysiological role in LC and other infectious lung diseases using a molecular approach. Numerous studies have reported the direct involvement of the host microbiome in lung tumorigenesis processes and their impact on current treatment strategies such as radiotherapy, chemotherapy, or immunotherapy. The genetic and metabolomic cross‐interaction, microbiome‐dependent host immune modulation, and the close association between microbiota composition and treatment outcomes strongly suggest that designing microbiome‐based treatment strategies and investigating new molecules targeting the common holobiome could offer potential alternatives to develop effective therapeutic principles for LC treatment. This review aims to highlight the interaction between the host and microbiome in LC progression and the possibility of manipulating altered microbiome ecology as therapeutic targets. Host–microbiome interaction in lung cancer. Both local (lung) and distal (gut) microbiota play critical roles in lung cancer